Tekst: "Int. Instituut voor Geschiedenis solidair!". Gebruikt tijdens FNV-demonstratie tegen Bestek'81. Met stokken (1979)
Tekst: "Int. Instituut voor Geschiedenis solidair!". Gebruikt tijdens FNV-demonstratie tegen Bestek'81. Met stokken.